Social stress and the reactivation of latent herpes simplex virus type 1 - Padgett, David A. (The National Academy of Sciences, 1998)
Psychological stress is thought to contribute to reactivation of latent herpes simplex virus (HSV). Although several animal models have been developed in an effort to reproduce different pathogenic aspects of HSV keratitis or labialis, until now, no good animal model existed in which application of a psychological laboratory stressor results in reliable reactivation of the virus. Reported herein, disruption of the social hierarchy within colonies of mice increased aggression among cohorts, activated the hypothalamic-pituitary-adrenal axis, and caused reactivation of latent HSV type 1 in greater than 40% of latently infected animals. However, activation of the hypothalamic-pituitary-adrenal axis using restraint stress did not activate the latent virus. Thus, the use of social stress in mice provides a good model in which to investigate the neuroendocrine mechanisms that underlie behaviorally mediated reactivation of latent herpesviruses.